Predictive biomarkers for response to omalizumab in patients with severe allergic asthma: a meta-analysis. Issue 9 (2nd September 2022) - Li, Yaqin; Li, Xiaoyan; Zhang, Biyu; Yu, Qing; Lu, Yanming
ABSTRACT: Background: Predicting omalizumab treatment response has been a challenge and significant aspect for selecting suitable severe allergic asthma patients for omalizumab use. Objective: To determine which domains of pretreatment baseline characteristics predict omalizumab treatment response among asthmatic patients. Methods: Electronic bases were searched for eligible studies that reported potential biomarkers that could predict omalizumab responsiveness and efficacy. Patients who accepted omalizumab treatment were stratified into responders and non-responders. WMD, OR, and their 95%CI were used to access the differences between those omalizumab receivers. Sensitivity analysis and subgroup analysis were conducted for potential heterogeneity. Results: A total of 41 studies evaluating efficacy predictors of omalizumab were included in this meta-analysis. The pooled results showed that omalizumab responders had significantly younger age in the adult subgroup, higher pretreatment total serum IgE level, percent predicted FEV1 and FeNO than that non-responder. We further confirmed that higher blood eosinophil counts and total serum IgE levels are useful markers for selecting asthma patients who may benefit more from omalizumab. Conclusions: Pre-treatment blood eosinophil counts and total serum IgE level can be a useful efficacy predictor in selecting allergic asthma patients for omalizumab treatment.